Reactive extraction of solid coconut waste to produce biodiesel - Sulaiman, Sarina; Abdul Aziz, A.R.; Aroua, Mohamed Kheireddine (Taiwan Institute of Chemical Engineers, 2013)
Biodiesel is an alternative diesel fuel produced using transesterification method where edible or non edible oil and alcohol reacts in the presence of catalyst. Biodiesel is expensive than fossil fuels because of higher raw material and production costs. Solid coconut waste is an alternative raw material from waste and suitable for biodiesel production to lower the production cost. Solid coconut waste is produced after coconut milk extraction and may still contain 17–24 wt% extractable oil content. This study introduces reactive extraction of solid coconut waste for biodiesel production. Effects of catalyst amount, KOH (0.8– 2.0%), temperature (55–65 8C) and mixing intensity (500–900 rpm) were studied to optimize the reactive extraction. Based on the Response Surface Methodology (RSM), the optimum condition was found to be 2.0 wt% of KOH catalyst, 700 rpm of mixing intensity and reaction temperature, 62 8C where resulted in 88.5% of biodiesel yield.